The Violent Origins of Law - Cavallo, Riccardo (Filozoficzne Aspekty Genezy, 2022)
The aim of this article is to analyse an issue discussed by philosophers and legal scholars since ancient times: the violent origins of law. In other words, it attempts to respond to the following questions: can we ultimately trace the origins of law back to violence, and could it be that law is in fact a continuation of violence by other means? To this purpose, there will be retraced the law-violence relation as portrayed in the Greek tragedy The Eumenides where Aeschylus focuses on Orestes’ trial, is of particular relevance when it comes to questioning the origins of law. At the same time, there will be followed the footsteps of Michel Foucault and Walter Benjamin who had the undoubted merit of having brought to light, within the tragic framework of the twentieth century, the relationship between law and violence.